2020
DOI: 10.1111/bcp.14593
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiol in infantile haemangioma: A paediatric post‐marketing surveillance drug study

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The trial evaluated the safety, effectiveness, tolerance, and cardiological changes. The results obtained showed that no severe adverse events occurred in the rapid protocol and that there was good cardiac tolerance [ 63 ].…”
Section: Propranolol As Adjuvant Therapy At Single Administration In ...mentioning
confidence: 99%
“…The trial evaluated the safety, effectiveness, tolerance, and cardiological changes. The results obtained showed that no severe adverse events occurred in the rapid protocol and that there was good cardiac tolerance [ 63 ].…”
Section: Propranolol As Adjuvant Therapy At Single Administration In ...mentioning
confidence: 99%
“…This is the largest study objectively assessing sleep in infants treated with propranolol for IH. Our data show that propranolol exposure mainly affects infants' nighttime sleep [2,[4][5][6][7] and publications on adult patients reporting increased nighttime awakenings, insomnia, and nightmares while on propranolol and other beta-blockers [40][41][42][43]. However, infant 24-hour Total Sleep was not affected by propranolol.…”
Section: Discussionmentioning
confidence: 52%
“…As a lipophilic molecule, propranolol can cross the blood-brain barrier, leading to concerns for a potentially negative impact on central nervous system (CNS) function [3,4]. Indeed, parents have reported sleep disturbances such as insomnia, night restlessness, hypersomnia, and nightmares/night terrors in up to 30% of treated infants [2,[5][6][7][8]. Intolerable sleep problems are the most frequent reason for early propranolol discontinuation, which may result in a poorer overall outcome of treated IH [9].…”
Section: Introductionmentioning
confidence: 99%
“…The common adverse events associated with propranolol (hypoglycemia, hypotension, bradycardia, and bronchospasm) infrequently occurred, with no significant difference in frequency over placebo [ 62 ]. Postmarketing surveillance drug study supports the efficacy and good tolerance of propranolol (Hemangiol) in children with infantile hemangioma [ 64 ].…”
Section: Truly Repurposed Cancer Drugs Whose First Regulatory Labelin...mentioning
confidence: 99%